From Lithuanian Riflemen to Forest Brothers: Research on the Development of the Local Military Structure - Noreika , Dainius (Genocidas ir rezistencija, 2012)
The article analyses the Thorn Company, a partisan unit that operated in northeast Lithuania, and the link of its partisans with the previously established societal tradition of self-defence and armed activity. The author seeks to reveal the extent to which the partisans belonged to the pre-war Lithuanian Riflemen’s Union and protective squads of small towns and villages which were formed during the uprising of 1941 as well as their participation in the divisions of public and auxiliary police which operated in 1941–1944. The research was carried out using analytical, inductive and statistical methods.The tradition of armed resistance and self-defence had been maturing in the territory of the future area of activity of Thorn Company (Zarasai regional district, Salakas village area). This tradition had been developing ever since the fights for independence in the early part of the twentieth century. Even then the local population who formed a squad of saboteurs actively assisted the Lithuanian army. The mindset of armed resistance to invaders was shaped, their skills of armed fighting were improved, and a framework of self-defence was taking shape. The memory and traditions of freedom fighting were nourished and passed on to the younger generation throughout the two decades of Lithuanian independence in the riflemen’s squadrons, which operated in the Salakas village district. This tradition determined an active role for riflemen from Salakas area in the anti-Soviet June uprising of 1941, and in their participation in policing units during the period of Nazi occupation (the latter activity was determined by anti-Soviet rather than pro-Nazi convictions).The military activity tradition shaped in the context of the above mentioned events was also alive in the postwar period. Throughout the whole period of the military company’s existence, its backbone was made up of fighters who gained fighting experience in riflemen’s squadrons during the independence period as well as in the Naziperiod police and self-defense divisions. Many ff them served in earlier military formations of earlier periods, and thus presumably cherished a certain collective mindset, made up of patriotism, belief in the possibility of restoring Lithuanian sovereignty and a deep anti-Soviet disposition. They must have been inclined to think that the gun was a reliable means of survival, and armed fighting was the most suited form of relating to the occupiers.
Keywords: Soviet occupation; armed resistance; partisans; riflemen